Semi-continuous casting of magnesium alloy AZ91 using a filtered melt delivery system - Mainul Hasan; Latifa Begum (Journal of Magnesium and Alloys, 2015)
A 3-D numerical simulation of an industrial-sized slab caster for magnesium alloy AZ91 has been carried out for the steady state operational phase of the caster. The simulated model consists of an open-top melt delivery system fitted with a porous filter near the hot-top. The melt flow through the porous filter was modeled on the basis of Brinkmann-Forchimier-Extended non-Darcy model for turbulent flow. An in-house 3-D CFD code was modified to account for the melt flow through the porous filter. Results are obtained for four casting speeds namely, 40, 60, 80, and 100 mm/min. The metal-mold contact region as well as the convective heat transfer coefficient at the mold wall were also varied. In addition to the above, the Darcy number for the porous media was also changed. All parametric studies were performed for a fixed inlet melt superheat of 64 °C. The results are presented pictorially in the form of temperature and velocity fields. The sump depth, mushy region thickness, solid shell thickness at the exit of the mold and axial temperature profiles are also presented and correlated with the casting speed through regression analysis.